PROMOTING THE USE OF MOBILE DEVICES FOR E-LEARNING SOLUTIONS: DEVELOPING AN ANDROID APP FOR NATIONAL OPEN UNIVERSITY OF NIGERIA - Samuel, Owodunni Ayanda; Jadesola, Owolabi Modupe (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
E-Learning is a broad and relatively novel concept that covers the use of electronic devices in delivering formal education. This research work aims to consider some of the diversities entailed and some of the specific ways that electronic devices can promote learning. Of particular interest is the use of mobile devices, considering the contemporary surge in smartphones and the roles these can play in individualized learning. The shift in possibilities, as well as the seemingly endless options available, are some of the concepts explored in this work. The android app developed is primarily to show the prospects of establishments such as National Open University of Nigeria (NOUN) which offer strictly open and distance learning that mobile devices can be used to promote learning. This will be shown to be innumerable and could easily validate many more studies in this field. The application (app) developed in this project was for an android device, which by far is the most common mobile operating system available presently. The procedure involved the use of android studio which provides an environment for coding and testing apps on an android phone. The widespread preference, as well as the ubiquitous occurrence of android based smartphones, was the factor behind this platform choice.